Changes of Somatic Characters Among Students of Wroclaw Polytechnics - Elżbieta, Elżbieta (Anthropological Review, 1983)
The paper presents an analysis of changes in absolute values of morphological characters and body proportions of male and female students of a technical college. Analysis is based on longitudinal measurements; 290 males and 244 females were measured thrice during a year. On grounds of analysis encompassing 25 somatic characters and 14 quotient indices uneven increases of various body parameters have been shown. Greatest changes occured in elements of stoutness, ie. various breadths, circumferences and skinfolds. Sexual dimorphism concerned: mostly the same characters. In males the most significant changes are those of upper body.